ANALISIS PRODUKTIVITAS ALAT BERAT PADA PEMBANGUNAN MARINA CENTER UNIVERSITAS PATTIMURA TAHAP II DI DESA HILA - Heny Sihasale; Lenora Leuhery; Henriette Dorothy Titaley (Jurusan Teknik Sipil, 2023)
A heavy equipment productivity review was carried out on the Unpatti Ambon Marina Center Development project road section from STA 00+000 to STA 00+900 m. The analysis method are calculating the productivity of heavy equipment for excavation and embankment work, highway paving and reviewing the costs of using each heavy equipment in the form of excavators, dump trucks, wheel loaders, vibration rollers, motor graders, tandem rollers, water tank trucks, asphalt mixing plants and asphalt finisher. The analysis results show that for the primary channel, the excavation volume is 729.30 m³ and the embankment volume is 265.20 m³. For secondary channels, the excavation volume is 709.79 m³ and the embankment volume is 236.60 m³. The productivity of heavy equipment in the form of excavators in excavation work is 122.52 m³/hour and earth moving work is 173.67 m³/hour. For wheel loader productivity, the work of transferring material to the dump truck is 987.7 m³/hour and the work of transferring material to the asphalt mixing plant is 52,359 m³/hour. Meanwhile, the productivity of the motor grader for overlay leveling work is 3352.94 m²/hour, for solid overlay leveling work is 419,117 m²/hour, and for stripping work it is 3352.94 m²/hour. The productivity of the vibration roller is 92.13 m³/hour, the truck water tank is 71,142 m³/hour, the tandem roller is 32.21 m³/hour, the asphalt mixing plant is 49.80 tons/hour and the asphalt finisher is 23,530 m³/hour. The operating costs for heavy equipment for asphalt mixing plants are 462,852,825 Rp/hour, asphalt finishers are 118,106.48 Rp/hour, 3-5 ton dump trucks are 131,477.95 Rp/hour, excavators are 172,259.59 Rp/hour, motor graders are 174,731 .19 Rp/hour, tandem roller is 109,233.68 Rp/hour, vibration roller is 109,233.68 Rp/hour, water tank truck is 131,478.12 Rp/hour and wheel loader is 126,532.63 Rp/hour.